Exodermis and endodermis are the sites of xanthone biosynthesis in Hypericum perforatum roots. Issue 3 (6th December 2017) - Tocci, Noemi; Gaid, Mariam; Kaftan, Filip; Belkheir, Asma K.; Belhadj, Ines; Liu, Benye; Svatoš, Aleš; Hänsch, Robert; Pasqua, Gabriella; Beerhues, Ludger
Summary: Xanthones are specialized metabolites with antimicrobial properties, which accumulate in roots of Hypericum perforatum . This medicinal plant provides widely taken remedies for depressive episodes and skin disorders. Owing to the array of pharmacological activities, xanthone derivatives attract attention for drug design. Little is known about the sites of biosynthesis and accumulation of xanthones in roots. Xanthone biosynthesis is localized at the transcript, protein, and product levels using in situ mRNA hybridization, indirect immunofluorescence detection, and high lateral and mass resolution mass spectrometry imaging (AP‐SMALDI‐FT‐Orbitrap MSI), respectively. The carbon skeleton of xanthones is formed by benzophenone synthase (BPS), for which a cDNA was cloned from root cultures of H. perforatum var. angustifolium . Both the BPS protein and the BPS transcripts are localized to the exodermis and the endodermis of roots. The xanthone compounds as the BPS products are detected in the same tissues. The exodermis and the endodermis, which are the outermost and innermost cell layers of the root cortex, respectively, are not only highly specialized barriers for controlling the passage of water and solutes but also preformed lines of defence against soilborne pathogens and predators.